Tindak Pidana Aborsi dalam Perspektif Hukum Pidana Indonesia: Antara Larangan dan Pengecualian - Nadiyatul Khairiah (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
Abortion is a contentious legal and moral issue, as it involves two equally important rights: the right to life of the fetus and a woman's right to bodily autonomy and reproductive health. Under Indonesian criminal law, abortion is generally classified as a criminal offense, as stipulated in the Criminal Code (KUHP). However, exceptions are recognized under specific conditions such as medical emergencies and pregnancies resulting from rape, in accordance with Law Number 17 of 2023 on Health. This study aims to examine the legal boundaries between prohibited and permitted abortions and to analyze the challenges of implementing these provisions in practice. The findings indicate that despite the existence of legal exceptions, implementation remains difficult due to complex procedures, limited facilities, and inadequate understanding among law enforcement and health workers. Therefore, clear technical regulations and cross-sectoral education are essential to ensure fair legal protection for both women and medical professionals.